Preparation of metal-organic framework-derived Fe-CoZnCN-T nanocomposites and their microwave absorption performance - Ren, Shuning; Ju, Pengfei; Yu, Haojie; Nan, Bohua; Wang, Li; Lian, Aizhen; Zang, Xusheng; Liang, Hongyu (Materials research bulletin, 2025)
•When the Fe-CoZnCN-T composites are mixed in solid paraffin with 30 wt% filler content, Fe-CoZnCN-700 exhibits good impedance matching ability and microwave loss ability due to the appropriate permittivity and permeability, thus exhibiting excellent microwave absorption performance.•The RLmin reaches −61.95 dB at the frequency of 15.20 GHz, the effective absorption bandwidth is greater than 5.42 GHz, and the matching thickness is only 2 mm. With advancing technology, electromagnetic wave applications are expanding, yet associated radiation increasingly threatens precision instruments and human health, necessitating high-performance absorption materials. Metal-organic frameworks (MOFs) emerge as promising candidates due to their lightweight design, structural tunability, and porosity. This study synthesized three Fe-CoZnCN-T composites through Fc-ZIF-8@CoZn-ZIF pyrolysis at 700 °C, 800 °C, and 900 °C. Structural characterization via TEM/XRD/VSM/Raman revealed optimized dielectric/magnetic properties in Fe-CoZnCN-700. When blended with paraffin (30 wt%), this composite demonstrated exceptional impedance matching and wave dissipation. At 2 mm thickness, Fe-CoZnCN-700 achieved a minimum reflection loss of -61.95 dB at 15.20 GHz with >5.42 GHz effective bandwidth, outperforming counterparts processed at higher temperatures. The balanced permittivity-permeability synergy in 700 °C-derived material underscores its potential for ultrathin microwave absorbers in GHz-range applications. [Display omitted]